Constructing bilingual input safe spaces at home: rethinking exposure to language from a multilingual and multisite perspective on literacy practices - Costa Wätzold, Juliane; Melo-Pfeifer, Sílvia (Frontiers in Language Sciences, 2024)
Introduction This article analyses parents' and children's attitudes toward the different literacy practices across three different contexts (at home, in a community project, and, indirectly, at school) and how they perceive the interaction between these practices and the development of competences in the Heritage Language (HL). We investigate the relevance of family and community, and how mainstream school influences the co-construction of literacy practices that affect the development of HL, while at the same time supporting the development of the majority language, and especially in broadening the understanding of the notion of language exposure. Methods Semi structured interviews with parents and focus groups with children (aged 4–14) were carried out in Munich, Germany, between May 2018 and February 2020. Data from the verbal interactions, in a total of 12 h of recorded audio with the parents and 8h with the children, was transcribed and the excerpts were coded in Nvivo. In a first moment, a data and theory driven thematic analysis with open data coding was undertaken; subsequently, discourse analysis was used to analyze selected excerpts individually and reconstruct the meaning the participants were attaching to their literacy practices. Three thematic strands were identified. Results We make the case that exposure to literacy practices in the majority language is interpreted and (re)appropriated by families and communities to support the development of complex and integrated literacy practices involving the different languages of children's repertoires. We shed light on how families construct bilingual input safe spaces at home, i.e., spaces where continuities between formal, informal and non-formal literacy practices in both German and Portuguese are assured. Discussion The results bring a critical perspective on the ecology of literacy practices and highlight the added value of seeing those practices interconnected holistically from a co-developmental viewpoint. Such interconnectedness has a potential positive impact not only in children's HL but also in the majority language, and possibly in the languages learnt at school.